Sulfur accumulation in gypsum-forming thiophores has its roots firmly in calcium - Robson, T.; Stevens, Jason; Dixon, Kingsley; Reid, N. (Elsevier BV, 2017)
Recent studies suggest sulfur-accumulators (thiophores and gypsophiles) produce foliar gypsum (CaSO4 2H2O) as a novel biomineralogical tolerance mechanism against sulfate salinity and excess soluble calcium (e.g. gypsic soil). However, little is known of the geochemical and ecophysiological aspects of foliar gypsum. The compositional, developmental (biomass, root development) and functional responses (photosystem performance and water relations), to soils with contrasting relative SO4 2 and Ca2+ pore-water concentrations (incl. a gypsum treatment), were examined in two gypsum-forming desert thiophores (Acacia bivenosa L. and A. ligulata A.Cunn. ex Benth.) and a sympatric non-thiophore comparator (A. ancistrocarpa Maiden & Blakely). Sulfur and calcium were accreted broadly as a function of the relative abundance of Ca2+ and SO4 2 ions in soil solution, and interspecific responses revealed thiophores are preferentially Ca accumulators, tending to maximise Ca uptake for the given conditions and scaling sulfate accumulation in relation to Ca, a co-regulation behaviour absent in the comparator. The thiophores were also sensitive to sulfur limitation, and these observations are consistent with cytosolic Ca2+ and SO4 2 regulation through gypsum precipitation. However, the gypsum-forming species were not comparatively tolerant to the gypsum treatment, most likely due to a lack of tolerance to limited P bioavailability resulting from the formation of sparingly-soluble calcium-phosphate soil minerals. The outcomes indicate that the capacity for gypsum biomineralisation does not, by itself, confer tolerance to the full suite of geochemical stress factors presented by gypsic soils (e.g. constrained P bioavailability). The findings steer future research towards testing alternative hypothesis pertaining to the ecophysiological basis of gypsum formation (e.g. osmoregulation) as well as examining whether obligate gypsophiles, which are also challenged by constrained P bioavailability, benefit by forming gypsum biominerals.